Assessment of gDNA extracted from Staphylococcus aureus isolate by polymerase chain reaction, agarose gel electrophoresis, and spectrophotometric assay - Ricky Acanto; Jasmin Castor; Mary Grace Langcoy (Philippine Association of Institutions for Research, Inc., 2021)
DNA sequencing is crucial in molecular biology techniques to identify Staphylococcus aureus isolates' genotype to advance diagnoses, prevent, and control infections. DNA isolation can be influenced by several factors which can affect the quality of the output. The experiment was conducted to assess the quality and quantity of genomic DNA isolated from S. aureus. The gDNA's purity and concentration were determined using the spectrophotometric assay, and the quality was analyzed using PCR and agarose gel electrophoresis. The purity of DNA and RNA was determined using the absorbance ratio at A260 and A280, and the percent coefficient of variation was used for the three replicates. The result showed that the extracted gDNA from S. aureus was obtained in large quantities, with good quality, R1=93.67 µg/ml, R2=59.85 µg/ml, and R3=67.50 µg/ml. The concentration was within a 1.8 - 2.0 absorbance ratio and was considered high quantity output. The extracted and amplified pure gDNA fragment from the sample can now be used for other molecular techniques.